1995
DOI: 10.1111/j.1476-5381.1995.tb15906.x
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence from functional studies for somatostatin receptor heterogeneity in guinea‐pig isolated ileum, vas deferens and right atrium

Abstract: 1 Somatostatin (SRIF) causes a concentration-dependent inhibition of neurotransmission in guinea-pig ileum and vas deferens as well as negative inotropy in guinea-pig isolated right atrium. The SRIF receptors mediating these effects have now been further characterized by use of the peptides BIM-23027, BIM-23056 and L-362855, reported as selective for the recombinant SRIF receptor types, sst2, sst3 and sst5, respectively. 2 BIM-23027 was a highly potent agonist at causing an inhibition of neurotransmission in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
1
10
1
Order By: Relevance
“…Although EC 50 values could not be calculated, lower concentrations of octreotide and BIM-23027 than of SRIF were necessary to inhibit MMCs, consistent with an action at sst 2 receptors. BIM-23027 was about three times more potent than SRIF at inhibiting neurogenic contractions of the guinea pig ileum (15), and a similar potency order was observed for sst 2 -mediated inhibition of rat parietal cell secretion (43) and rat colon contractions (33).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although EC 50 values could not be calculated, lower concentrations of octreotide and BIM-23027 than of SRIF were necessary to inhibit MMCs, consistent with an action at sst 2 receptors. BIM-23027 was about three times more potent than SRIF at inhibiting neurogenic contractions of the guinea pig ileum (15), and a similar potency order was observed for sst 2 -mediated inhibition of rat parietal cell secretion (43) and rat colon contractions (33).…”
Section: Discussionmentioning
confidence: 78%
“…Octreotide and BIM-23027 are agonists with some selectivity for the sst 2 receptor, but each has additional agonist activity at sst 5 receptors, whereas Cyanamid154806 (Cyn) and BIM-23056 are antago-nists for sst 2 and sst 5 receptors, respectively (2,42). In this respect, BIM-23027 has been shown to inhibit neurogenically mediated contraction in the guinea pig ileum (15), whereas octreotide modulates gastrointestinal motility in both animals and human tissue (29,40). The aims of this study were therefore to characterize the spontaneous peristaltic activity observed in isolated preparations of rat and mouse small intestine and to examine its modulation by SRIF and selective sst-receptor ligands.…”
mentioning
confidence: 99%
“…Similarly our experiments were designed on the basis of establishing equieective concentrations of the antagonists prior to assessing their potential to elicit contractions During the course of our experiments it became evident that both CTOP and MR-2266 caused a transient inhibition of the electrically-evoked contractions. In light of the report that CTOP (but not CTAP) possesses agonist activity at somatostatin receptors (Connor et al, 1997a), and that these receptors are present in the ileum (Fenuik et al, 1995), we investigated whether co-activation of a non-opioid receptor could account for the reduced responses to CTOP in overnight, morphine-exposed preparations of the ileum. Our results showed that somatostatin produced qualitatively similar responses to CTOP and that subsequent desensitization of the receptor reduced the eect of CTOP on electrically-evoked contractions.…”
Section: Discussionmentioning
confidence: 99%
“…Such compounds include BIM-23027, BIM-23056, and L-362855 which selectively bind with subnanomolar affinities to sst2, sst3, and sst5 receptors, respectively (Raynor et al 1993a, b). Currently, however, few studies have investigated the effect of these SRIF analogues in gastrointestinal preparations naturally expressing SRIF receptors (McKeen et al 1994a;Feniuk et al , 1995. In the present study, the pharmacological properties of the SRIF receptor type mediating the antisecretory action of SRIF in rat colonic mucosa were studied by examining the actions of several selective SRIF analogues including BIM-23027, BIM-23056 and L-362855.…”
Section: Introductionmentioning
confidence: 99%